An alternative Bayesian statistics for probabilistic earthquake prediction in Mexico, Central and South America - GALANIS, O. CH.; TSAPANOS, T. M.; PAPADOPOULOS, G. A.; KIRATZI, A. A. (Bulletin of the Geological Society of Greece, 2001)
The probabilities of occurrence of strong (M>6.5) earthquakes, in the seismically active regions of Mexico, central and south America, are estimated. The straightforward approach of Bayes statistics is applied in order to search for the inter-arrival times of strong earthquakes in predefined seismic zones of the above referred regions. The method introduced allows to determine the uncertainties involved, which are expressed as percentages of the earthquake mean return period. The determination in this way is very efficient because one may calculate uncertainties on the same time scale. It is also shown that the final maximum Bayesian probabilities of the inter-arrival times in the several seismic zones are dependent on the data set used and particularly on its time length. Comparisons between the predicted and the real time of earthquake occurrences are finally made in order to evaluate the correlation between them.